2015
DOI: 10.1007/s11999-014-3668-9
|View full text |Cite
|
Sign up to set email alerts
|

The John Insall Award: Morbid Obesity Independently Impacts Complications, Mortality, and Resource Use After TKA

Abstract: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
5
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(138 citation statements)
references
References 33 publications
(48 reference statements)
6
123
5
4
Order By: Relevance
“…Morbid obesity and malnutrition are thought to be associated with more frequent perioperative complications in patients after TKA [5,6,10,12,31]. In addition, both often are considered modifiable risk factors, and some surgeons suggest that they should be corrected before elective TKA [1,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morbid obesity and malnutrition are thought to be associated with more frequent perioperative complications in patients after TKA [5,6,10,12,31]. In addition, both often are considered modifiable risk factors, and some surgeons suggest that they should be corrected before elective TKA [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of TKA in populations at greater risk for complications are less well defined. Morbid obesity and malnutrition have been shown to be associated with increased perioperative complications after TKA [5,6,10,12,16,18,19,27,32]; however, some studies have not shown an increased risk of perioperative complications in patients who are morbidly obese [3,13,14,23,25]. In addition, patients with morbid obesity are more likely to be malnourished than patients who are not obese, raising the question whether morbid obesity, malnutrition, or both, are independently associated with increased perioperative complications [12].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have also evinced the influence of patient comorbidities on the utilization of resources such as office visits, emergency department (ED) visits, length of stay, drug costs, procedures, and overall costs in other study populations [33][34][35][36][37] .…”
Section: Case: the Cholecystectomy And Contributors To Resource Usementioning
confidence: 99%
“…As has been the case every year for nearly two decades now, the partnership between CORR 1 and the Knee Society has produced a collection of papers that should influence thought on the most important current issues in the treatment of the adult knee. While we could feature any of the dozens of papers from those proceedings in the spotlight section, including any of several award-winners [1,3,4], we have chosen to highlight a paper by Professor Fares S. Haddad's group in the United Kingdom on a thorny and resistant topic: Single-stage exchange revision for the infected TKA.…”
Section: T Is With Great Pride That Clinicalmentioning
confidence: 99%